Low power, high ambitions: New ventures developing their first supply chains. Issue 1 (January 2021) - Bjørgum, Øyvind; Aaboen, Lise; Fredriksson, Anna
Abstract: This paper investigates sourcing decisions for new ventures. Sourcing decisions are especially problematic for start-ups because they lack resources, knowledge and legitimacy to evaluate and interact with suppliers. We develop and apply a framework that connects global sourcing, relationship development and attractiveness. Further, we investigate how new ventures develop their first supply chains by conducting an exploratory multiple case study of six Norwegian start-ups. Based on our findings, we develop three propositions regarding how start-ups mediate their lack of attractiveness through pre-sales and by choosing shorter supply chains and smaller suppliers. The implications for practice include emphasizing the importance of developing a business relationship with the supplier in parallel with making sourcing decisions. This study is a novel contribution to an underexplored topic, and we conclude by proposing a research agenda for future explorations of start-ups and supply chain development. Highlights: Investigates how start-ups develop (global) supply chains using a multiple case-study. Framework combines global sourcing and business-to-business relationship development. Develops propositions on how new ventures mediate their lack of attractiveness. Proposes a research agenda related to start-ups and supply chain development.